Agriculture at a Crossroads: The Global Report - D. Mclntypre Beverly (MC Graw Hill, 2009)
The International Assessment of Agricultural Knowledge, Science, and Technology for Development (IAASTD) looks realistically at how we could effectively use agriculture/AKST to help us meet development and sustainability goals. An unprecedented three-year collaborative effort, the IAASTD involved more than 400 authors in 110 countries and cost more than